2018
DOI: 10.1021/acsami.8b10645
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrodeposition of Cobalt Sulfide Nanosheet Arrays on Carbon Cloth as a Highly Efficient Bifunctional Electrocatalyst for Oxygen Evolution and Reduction Reactions

Abstract: As one of the advanced cobalt-based materials, cobalt sulfides with novel architecture have attracted huge interest due to the low cost, easy availability, and promising bifunctional activity for both the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), which is essential for next-generation energy storage devices. Herein, we demonstrated a facile and clean electrochemical technique to directly synthesize CoS nanosheets with high purity onto the surface of carbon cloth, and a quick thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 36 publications
(81 reference statements)
2
65
0
Order By: Relevance
“…Studies have shown that Co/Ni based materials exhibited high electrocatalytic OER activity in alkaline solutions . These materials included cobalt (nickel) oxides/hydroxide, Co(Ni)Fe layered double hydroxides (LDHs), cobalt (nickel) molybdate, cobalt (nickel) sulfides, cobalt (nickel) selenides, cobalt (nickel) nitrides, and cobalt (nickel) phosphides . However, due to the low active surface area and the poor electrical conductivity, the performance of these electrocatalysts still does not meet the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Co/Ni based materials exhibited high electrocatalytic OER activity in alkaline solutions . These materials included cobalt (nickel) oxides/hydroxide, Co(Ni)Fe layered double hydroxides (LDHs), cobalt (nickel) molybdate, cobalt (nickel) sulfides, cobalt (nickel) selenides, cobalt (nickel) nitrides, and cobalt (nickel) phosphides . However, due to the low active surface area and the poor electrical conductivity, the performance of these electrocatalysts still does not meet the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100] Encapsulation of TM compounds including alloys, hydroxides, sulfides, phosphates and nitrides nanoparticles in N-doped carbon is also an effective method to generate materials rich in electrocatalytic active sites. [68,[101][102][103][104][105][106][107][108] The N-doped carbon effectively facilitates the electron transport and prevents the aggregation of nanoparticles. [68,101] The synergistic effect of TM compounds in contact with carbon materials can improve electron transfer capability, thus promoting catalytic efficiency and stability of ORR and OER.…”
Section: Tm-based Nanoparticles Supported On the Heteroatom-doped Carbonmentioning
confidence: 99%
“…[68,101] The synergistic effect of TM compounds in contact with carbon materials can improve electron transfer capability, thus promoting catalytic efficiency and stability of ORR and OER. [102][103][104][105][106][107][108] Gupta et al [15] synthesized highly active and stable graphene tubes decorated with FeCoNi alloy nanoparticles (Figure 10a). It was found that the unique structure of the graphene tube provides the maximum electrochemical accessible surface area, and together with the optimal graphitization degree and pyridinic nitrogen content significantly contributes to the activity and durability of the catalyst.…”
Section: Tm-based Nanoparticles Supported On the Heteroatom-doped Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, considerable attempts have been made to develop a variety of noble‐metal‐free catalysts. For example, transition metal phosphide, chalcogenides,, oxides,, carbides,, nitrides,, transition metal nitrogen‐containing complexes , . Among these candidates, transition metal carbides (TMC), such as Mo 2 C, Fe 5 C 2 and WC, have attracted a great attention due to their Pt‐group‐metals‐like electronic configuration and catalytic properties, while significantly reducing costs .…”
Section: Introductionmentioning
confidence: 99%